1998
DOI: 10.1258/0956462981921053
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of alcohol use and its association with STD/HIV-related risk practices, attitudes and knowledge among an AfricanAmerican community-recruited sample

Abstract: The aim was to determine the association between frequency of alcohol use in the past 30 days and HIV-related risk behaviours among adults in an African-American community. Data were collected by trained street outreach workers, from 522 persons in 4 areas selected on the basis of 7 health and criminal justice indicators of high risk for HIV, STD and substance abuse, and drug-related arrests. A survey assessed demographics, substance use, sexual behaviour, HIV knowledge, attitudes and depression. Subjects repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 13 publications
4
25
2
Order By: Relevance
“…This may be a better indicator of the influence of alcohol on safer sex than just the use of alcohol, which does not properly take into account the volume of intake. This finding concurs with several other findings, where alcohol use by either FSW themselves or their sexual partners increases the risk of non condom use (5,10,(12)(13)(14)(15)(16). In the four country study mentioned previously, alcohol consumption was not found to be associated with condom use in men.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be a better indicator of the influence of alcohol on safer sex than just the use of alcohol, which does not properly take into account the volume of intake. This finding concurs with several other findings, where alcohol use by either FSW themselves or their sexual partners increases the risk of non condom use (5,10,(12)(13)(14)(15)(16). In the four country study mentioned previously, alcohol consumption was not found to be associated with condom use in men.…”
Section: Discussionsupporting
confidence: 91%
“…For women, drinking alcohol more than once a week was found to be associated with a decreased rate of condom use in Yaoundè. Other studies have shown that regular alcohol use or the presence of a drinking problem is one of the strongest predictors of non condom use when visiting a FSW or other non regular sexual partners (15)(16)(17). In the present study, Khat use was not found to be significantly associated with condom use.…”
Section: Discussioncontrasting
confidence: 74%
“…As shown in other studies (Morrison, DiClemente, Wingood, & Collins, 1998;Nadeau, Truchon, & Biron, 2000), drug and alcohol use were associated with risky sexual behavior in bivariate analyses, and drug use remained associated in multivariate analysis. However, alcohol use dropped out of the multivariate model, likely due to the highly significant positive relationship between drug and alcohol use.…”
Section: Discussionsupporting
confidence: 81%
“…Alcohol use has been associated with various sexual risktaking behaviors, including having multiple sex partners [1], and low condom use [2][3][4][5][6][7][8]. In a qualitative study linking alcohol use and sexual risk behavior across eight countries including Russia, Kenya, and India, the World Health Organization (WHO) identified a number of interactions between alcohol use and sexual behaviors, including using alcohol-selling venues as meeting places for sexual partners, and using alcohol during first sexual encounters [9].…”
Section: Introductionmentioning
confidence: 99%